P3 mAb: An Immunogenic Anti-NeuGcGM3 Antibody with Unusual Immunoregulatory Properties - Martínez, Darel; Rodríguez, Nely; Griñán, Tania; Rondón, Teresa; Vázquez, Ana M.; Pérez, Rolando; Hernández, Ana María (Frontiers in Immunology, 2012)
P3 is a murine IgM mAb that recognize N-glycolilated gangliosides, sulphatides and antigens expressed in melanoma, breast and lung human tumors. This antibody has the ability to trigger an IgG antibody response in the syngeneic BALB/c model, even when it is administered in the absence of adjuvant or carrier protein. The mechanism by which the P3 mAb, a self immunoglobuline, induce this immune response in the absence of co-stimulatory or classical danger signals is still unknown. In the present paper we show that the high immunogenicity of P3 mAb depends not only on CD4 but also on CD8+ T cells, since the depletion of CD8+ or CD4+ T cells led to the loss of P3 mAb immunogenicity in the syngeneic model. Furthermore, the immunization with P3 mAb enhanced the recovery of the CD8+ T cell population in mice treated with an anti-CD8a antibody. Additionally, the immunization with P3 mAb restored the capacity of immunosuppressed mice to reject allogeneic tumors, a mechanism mediated by the action of CD8+ T cells. Finally, in mice with cyclophosphamide induced lymphopenia, the administration of P3 mAb accelerated the recovery of both CD4+ and CD8+ T cells. These results show new possibilities for B and CD8+ T cells interactions during the immune response elicited by a self-protein. Furthermore they point to P3 mAb as a potential interesting candidate for the treatment of immunosuppressed patients.